Design, Construction, and Implementation of a Magnetic Resonance Elastography Actuator for Research Purposes. Issue 3 (14th March 2022) - Triolo, Emily Rose; Khegai, Oleksandr; Ozkaya, Efe; Rossi, Nicholas; Alipour, Akbar; Fleysher, Lazar; Balchandani, Priti; Kurt, Mehmet
Abstract: Magnetic resonance elastography (MRE) is a technique for determining the mechanical response of soft materials using applied harmonic deformation of the material and a motion‐sensitive magnetic resonance imaging sequence. This technique can elucidate significant information about the health and development of human tissue such as liver and brain, and has been used on phantom models (e.g., agar, silicone) to determine their suitability for use as a mechanical surrogate for human tissues in experimental models. The applied harmonic deformation used in MRE is generated by an actuator, transmitted in bursts of a specified duration, and synchronized with the magnetic resonance signal excitation. These actuators are most often a pneumatic design (common for human tissues or phantoms) or a piezoelectric design (common for small animal tissues or phantoms). Here, we describe how to design and assemble both a pneumatic and a piezoelectric MRE actuator for research purposes. For each of these actuator types, we discuss displacement requirements, end‐effector options and challenges, electronics and electronic‐driving requirements and considerations, and full MRE implementation. We also discuss how to choose the actuator type, size, and power based on the intended material and use. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Design, construction, and implementation of a convertible pneumatic MRE actuator for use with tissues and phantom models Basic Protocol 2 : Design, construction, and implementation of a piezoelectric MRE actuator for localized excitation in phantom models